Web Platform for Georeferenced Telemonitoring: A Case Study on Elderly Healthcare - Barboza, Orlando; Florez, Andres; Viloria-Nuñez, Cesar; Gomez-Ceron, Diego (EASI: Engineering and Applied Sciences in Industry, 2025)
The monitoring and management of biomedical variables remain critical areas of focus within the scientific and technological fields. The increasing prevalence of cardiac conditions and the risks associated with geographic disorientation among the elderly population highlight a pressing challenge. This study presents a web-based platform designed to receive real-time biomedical data for assessing patient health status. To achieve this, the variables were simulated to define the necessary data structure. All data generated through an Android-based device were transmitted over a cellular network and stored in a preconfigured Cloud database, enabling the creation of a consultable historical record for future use. The platform was subsequently evaluated by 50 users, who shared their insights and rated aspects such as usability, interface design, and functionality through a detailed survey.
Keywords: Cardio; Georeferenced Telemonitoring; Web Platform